FACTORS THAT AFFECT THE QUALITY OF THE GOVERNMENT'S FINANCIAL STATEMENTS IN MEDAN - Handayani, Fitri (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to determine and analyze the factors that affect the quality of the Medan city government's financial statements. The independent variables used in this study are the application of Government Accounting Standards, the use of Regional Financial Accounting Information System, internal audit roles and functions, HR competencies and compliance with laws and regulations. The population in this study was 64 local government work units in Medan city government using saturated sampling techniques. This research was conducted by distributing 128 questionnaires to Medan City Local government work unit. This study uses SmartPLS as a tool for testing data. The results showed that the application of Government Accounting Standards and compliance with laws and regulations had a significant negative effect on the quality of local government financial reports. HR competency has no significant positive effect on the quality of the Medan city government financial statements. While the use of Regional Financial Accounting Information System and the role and function of internal audit have a significant positive effect on the quality of the Medan municipal government financial reports.